Guide To Greek Theatre And Drama. - McLeish, Kenneth (Plays and Playwrights., 2014)
A new and definitive guide to the theatre of the ancient world The Guide to Greek Theatre and Drama is a meticulously researched and accessible survey into the place and purpose of theatre in Ancient Greece. It provides a comprehensive author-by-author examination of the surviving plays of Aeschylus, Sophocles, Euripides, Aristophanes, and Menander, as well as giving an insight into how and where the plays were performed, who acted them out, and who watched them. It includes a fascinating discussion of the function of the essential characteristics of Greek drama, including verse, rhetoric,